(NhOVDENIE PO MUKAM(B: [(NrOMAN(B];s (NsESTRY(B: [(NrOMAN(B] / s (N~ASTX (B5s - (NtOLSTOJ(B, (NaLEKSEJ nIKOLAEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1983)
(Nw PQTYJ TOM WO[LI DWE PERWYE ^ASTI TRILOGII a(B. (Nn(B. (NtOLSTOGO (B"(NhOVDENIE PO MUKAM(B": "(NsESTRY(B" (NI (B"(NwOSEMNADCATYJ GOD(B".s
(NwOSEMNADCATYJ GODs
rus
Keywords: (NrOMAN(B-(N\POPEQs